Transitioning to online learning during COVID-19 Pandemic: Case study of a Pre-University Centre in Malaysia - Ahmad Alif, Kamal; Norhunaini, Mohd Shaipullah; Liyana, Truna; Muna, Sabri; Syahrul Nizam, Junaini (Science and Information Organization, 2020)
In the last decade, online learning has grown rapidly. However, the outbreak of coronavirus (COVID-19) has caused learning institutions to embrace online learning due to the lockdown and campus closure. This paper presents an analysis of students' feedback (n=354) from the Centre of Pre-University Studies (PPPU), Universiti Malaysia Sarawak (UNIMAS), Malaysia, during the transition to fully online learning. Three phases of online surveys were conducted to measure the learners' acceptance of the migration and to identify related problems. The result shows that there is an increased positivity among the students on the vie of teaching and learning in STEM during the pandemic. It is found that online learning would not be a hindrance, but blessing towards academic excellence in the face of calamity like the COVID-19 pandemic. The suggested future research direction will be of interest to educators, academics, and researchers' community.